ANALISIS PENERAPAN STANDARD OPERATING PROCEDURE (SOP) PENYIMPANAN BARANG PERISHABLE DI COLD KITCHEN HOTEL SANTIKA PREMIERE JOGJA - Nisa Rahmaniyah Utami; Wildan Rizky Rahadian; Rani Wahyuningsih Jahrotun (Bogor Hospitality Journal, 2024)
Storage system is a way to preserve goods to make it easier to do work. A hotel must oversee the storage system of the perishable materials it manages. This study aims to determine how far the implementation of the SOP is in the process of storing perishable goods in the Cold Kitchen section of Santika Premiere Jogja Hotel which includes storage of goods, storage methods, obstacles faced in this case the theory in reference to Bakri, Intiati, & Widartika's (2018). The details were collected using observation, interview and documentation techniques. Based on the results of the study, it was found that the Cold Kitchen section of Santika Premiere Jogja Hotel did not carry out the SOP for storing perishable goods as it should. Keywords : Cold Kitchen, Perishable, Storage